THE USE OF TIKTOK SOCIAL MEDIA BY STUDENTS OF SMA NEGERI 1 TEBING TINGGI IN CHOOSING BEAUTY PRODUCTS - Haiqal Dafala S; Nurhanifah Nurhanifah (Journal Analytica Islamica, 2026)
TikTok is increasingly being used by teenagers as a platform for information search and consumption reference, including in selecting beauty products. This study aims to describe the patterns of TikTok usage by female students at SMA Negeri 1 Tebing Tinggi in selecting beauty products and identify factors that influence their decisions. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Informants were purposively selected from female students in grades X–XII who actively use TikTok and use it as a reference for beauty products. Data were analyzed using thematic analysis through the stages of coding, categorization, and interpretation. The results show that TikTok serves as a primary reference source through product reviews, tutorials, and creator/influencer recommendations that shape female students' consumption preferences. Product selection decisions are influenced by creator credibility, viral trends, ease of access to information, and encouragement from the social environment. TikTok also contributes to the formation of female students' perceptions of beauty standards and self-identity in the digital space. Although it expands self-care knowledge and awareness, TikTok use has the potential to trigger impulsive consumption and pressure to adhere to ideal beauty standards. Therefore, strengthening media literacy is necessary so that adolescents can critically interpret content and make wiser consumption decisions.